Automating Home Appliances For Elderly and Impaired People: The B-Live Approach - Bartolomeu, Paulo (2012)
This paper describes the B-Live approach for automating home appliances for elderly and impaired people. This system has been developed at Micro I/O for enhancing the quality of life and the independence of its potential users. The target application is the retrofitting of common dwellings. The paper introduces the motivation for the B-Live system and presents a survey on current Smart Home projects and endeavours. The B-Live system is described and details on its software, hardware and communications architecture are provided. A survey of the supported appliances and interfaces is presented as well as a description of the B-live configuration and operation procedures. The suitableness of the B-Live system to improve the autonomy of the envisaged users was informally evaluated by C4, C5 and C6 patients at the CMRRC Rovisco Pais demonstrator. The conclusion is that the system has a short learning curve and can cope with the requirements of its potential users.